Chlorpromazine affects autophagy in association with altered Rag GTPase–mTORC1–TFEB signaling - Li, Ningning; Rao, Lingling; Zhao, Xueqing; Shen, Junwen; Su, Dan; Ma, Guoqiang; Sun, Shan; Ma, Qilian; Zhang, Li; Dong, Chunsheng; Tam, Kin Yip; Prehn, Jochen H. M.; et al. (Frontiers in Cell and Developmental Biology, 2023)
Autophagy is a critical protein and organelle quality control system which regulates cellular homeostasis and survival. Growing evidences suggest that autophagic dysfunction is tightly associated with many human diseases including neurological diseases and cancer. Among various autophagic regulators, MiT/TFE transcription factors, including transcription factor EB (TFEB), have been shown to act as the master regulators of autophagosomal and lysosomal biogenesis in both physiological and pathological conditions. According to the previous studies, chlorpromazine (CPZ), a FDA-approved antipsychotic drug, affects autophagy in diverse cell lines, but the underlying mechanism remains elusive. In our present study, we find that CPZ treatment induces TFEB nuclear translocation through Rag GTPases, the upstream regulators of mTORC1 signaling. Meanwhile, CPZ treatment also blocks autophagosome-lysosome fusion. Notably, we find significant accumulation of immature autophagosome vesicles in CPZ-treated cells, which may impede cellular homeostasis due to the dysfunction of autophagy-lysosome pathway. Interesting and importantly, our data suggest that expression of active form of Rag GTPase heterodimers is of help to reduce the accumulation of autophagosomes in CPZ-treated cells, further suggesting a major contribution of Rag GTPase-mTORC1-TFEB signaling axis to CPZ-induced autophagic impairment.